2017
DOI: 10.1371/journal.pone.0184337
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Endothelin 1, MCP-1 and Chromogranin A in patients with atrial fibrillation undergoing pulmonary vein isolation

Abstract: BackgroundThe relation between arrhythmias and stress is known. The aim of our current study was to elucidate whether plasma levels of previously described stress parameters are altered in highly symptomatic patients with atrial fibrillation (AF) per se and in patients undergoing ablation therapy by pulmonary vein isolation (PVI).Methods96 patients with AF undergoing PVI were recruited. Plasma levels of Endothelin-1 (ET-1), MCP-1 and Chromogranin-A (CGA) were measured before and three months after ablation com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…As reported in the clinical literature, pulmonary vein isolation is pivotal in radiofrequency ablation (RFA) to reduce signs and symptoms in patients with AF. 6 However, RFA may lead to recurrence of AF and is usually performed under sedation and in surgical conditions. The long immobilization time of RFA can weaken the patients' autonomous ventilation.…”
Section: Introductionmentioning
confidence: 99%
“…As reported in the clinical literature, pulmonary vein isolation is pivotal in radiofrequency ablation (RFA) to reduce signs and symptoms in patients with AF. 6 However, RFA may lead to recurrence of AF and is usually performed under sedation and in surgical conditions. The long immobilization time of RFA can weaken the patients' autonomous ventilation.…”
Section: Introductionmentioning
confidence: 99%
“…Three months post-CA, patients without new AF episodes exhibited a drop in ET-1 levels, nearly matching those of healthy individuals. In contrast, patients with AF recurrence showed unchanged ET-1 levels three months after CA [71]. However, other studies did not confirm these findings, showing no significant difference in ET-1 levels between the no-recurrence and recurrence groups (25.5 ± 4.4 vs. 26.7 ± 5.4; p = 0.286) [88].…”
Section: Long-term Rolementioning
confidence: 92%
“…Research evaluating endothelial function through biochemical markers like Endothelin-1 (ET-1) or mechanical parameters such as FMD has established a correlation between the state of the endothelium before CA and its success. Studies have consistently shown that ET-1 levels are higher in patients with persistent AF (PeAF) or paroxysmal AF (PAF) compared to healthy individuals [70][71][72]. Additionally, lower ET-1 levels were associated with a greater likelihood of maintaining AF-free status three months post-ablation [71], and ET-1 was identified as an independent risk factor for the postoperative recurrence of PeAF only [70].…”
Section: The Role Of Endothelial Dysfunction In Catheter Ablationmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the adrenergic system has a huge impact on the development of AF, the authors expected higher CGA levels as a surrogate for elevated sympathoadrenergic tone. 48,49 Lackermair et al explored the relationship between arrhythmias and stress, noting that the plasma levels of previously described stress parameters were altered in highly symptomatic patients with AF per se and patients undergoing ablation therapy by pulmonary vein isolation (PVI). In addition, CgA was lower in AF patients compared to healthy controls.…”
Section: Copeptinmentioning
confidence: 99%